Maqāṣid al-Sharīʿah as a Framework for Global Humanitarian Justice - Abdur Rohman; Muhammad Nor; Zainab Noor; Abd Rahman; Dewi Putriani Yogosara Lodewijk (Insani: Jurnal Pranata Sosial Hukum Islam, 2026)
The protection of human life and dignity must transcend legal boundaries to encompass a universal and inescapable moral responsibility. This study aims to analyse in depth how the principles of maqāṣid al-sharīʿah can be articulated as a normative foundation for global humanitarian justice, and how this concept can be implemented in response to various contemporary humanitarian challenges. This study employs a qualitative approach with a conceptual–normative analytical design, combined to a limited extent with exploratory empirical research. The results indicate that positioning maqāṣid al-sharīʿah as a framework for global humanitarian justice not only represents an effort to reinterpret the Islamic legal tradition but also offers an epistemological contribution to enriching global ethical discourse, which has predominantly been shaped by secular and technocratic approaches. Focused on the public interest, the protection of human dignity and substantive justice, the maqāṣid al-sharīʿah present a normative perspective that is more holistic, contextual and centred on human needs, thereby having the potential to serve as an alternative ethical foundation for responding to various contemporary humanitarian challenges in a fairer, more inclusive and sustainable manner.